Isolated Splenic Recurrence of Treated Jejunal Cancer: A Case Report with Brief Review of Literature - Agrawal, Chaturbhuj Ramanand; Sharma, Manish; Talwar, Vineet; Goel, Varun; Singh, Ajit Pratap (Indian Journal of Medical and Paediatric Oncology, 2019)
Spleen is a very infrequent site of metastasis despite the fact that it is the most vascular organ in the body. Even if systemic metastasis occurs, splenic metastasis largely remained asymptomatic due to its large functional reserve, and most often, the metastasis is detected incidentally on follow-up scan. Many cases of asymptomatic splenic metastasis detected on follow-up scans are reported in literature from different primary sites. Herein, we report a similar case of a 33-year-old male who presented with isolated splenic recurrence after a long treatment-free interval following curative treatment of adenocarcinoma jejunum. As stated, there are few previous reports of isolated splenic metastasis from carcinoma colon, but considering small intestinal adenocarcinoma, this is the first unique case reported to the best of our knowledge. Due to rarity of clinical scenario and lack of established guidelines, the treatment of such cases varies from patient to patient, and the knowledge, whatever we owe, is on the basis of case reports only.
Keywords: Adenocarcinoma jejunum; isolated splenic metastasis; splenectomy